Low‐cost bifunctional initiators for bidirectional living cationic polymerization of olefins. III. centrally functionalized polyisobutylenes. Issue 11 (12th March 2018) - Nugay, Turgut; Deodhar, Tejal; Nugay, Nihan; Kennedy, Joseph Paul
ABSTRACT: Allyl‐telechelic polyisobutylene (A‐PIB‐A) produced by the bis‐benzocyclobutane dichloride (bBCB‐diCl) initiator contains the bis‐benzocyclobutane (bBCB) fragment at the center of the macromolecule (A‐PIB‐bBCB‐PIB‐A). Thermolysis of A‐PIB‐bBCB‐PIB‐A quantitatively converts the central bBCB fragment to a substituted conjugated tetraene (A‐PIB‐tetraene‐PIB‐A). The structure of A‐PIB‐tetraene‐PIB‐A was anticipated from small molecule models and identified/quantitated by 1 H NMR spectroscopy. This is the first time a reactive functional group was introduced at the statistical center of a (telechelic) PIB. Subsequently, the A‐PIB‐tetraene‐PIB‐A was peroxidized to an epoxy derivative. Reaction of the A‐PIB‐tetraene‐PIB‐A with HSCH2 CH2 OH produced HOCH2 ‐telechelic PIB containing a central CH2 OH function, and hydrosilation with HSi(Me2 )‐O‐Si(Me2 )H produced SiH‐telechelic PIB with a central SiH function. Reactions with maleic anhydride, tetracyanoethylene, butyl lithium, and potassium permanganate have also been examined. In sum, A‐PIB‐bBCB‐PIB‐A and A‐PIB‐tetraene‐PIB‐A are useful intermediates for the synthesis of novel PIB‐based materials for various end uses under investigation. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 1140–1145 Abstract : Isobutylene polymerized by thebBCB‐diCl/TiCl4 difunctional initiating system and terminated byallyltrimethylsilane produces a polyisobutylene (PIB) with a centralbis‐benzocyclobutane (bBCB) fragment: A‐PIB‐bBCB‐PIB‐A. Heating quantitatively converts the bBCB initiator fragment at the center of the polymer to a substitutedtetraene : A‐PIB‐tetraene‐PIB‐A. This, the first centrally functionalizable telechelic PIB on record, was quantitatively converted by epoxidation, hydrosilation, and so on, to various useful derivatives.